Effectiveness of structured teaching program regarding child abuse on knowledge among mothers of school-age children at selected rural areas - ., Sanghpriya (International Journal Of Community Medicine And Public Health, 2020)
Background: Child abuse is a significant global problem with a serious impact on the victims throughout their lives. According to WHO (2013) which estimates that the international level of prevalence in child abuse and neglect was approximately 50500 children were at the risk of abuse right now. Objectives of the study was to assess the effectiveness of structured teaching program regarding child abuse. Methods: Research design was quasi experimental one group pre-test-post-test design used & setting was selected rural areas of Sarojini Nagar, Lucknow, UP. Samples 73 mothers were selected by purposive sampling technique. Tools were used as self-structured knowledge questionnaire. Results: Revealed that the mean score of the pre-test knowledge was 10.42 with SD of 1.95 whereas the mean score of the post-test knowledge score was 17.61 and SD was 1.7. Based on the findings researcher compared the calculated t value i.e. 21.05 and the tabulated value i.e.1.99 on 72 degrees of freedom at 0.05 level of significance. Since the calculated value was higher than the tabulated value the researcher rejected the null hypothesis and accepted the alternative hypothesis. Which revealed that there was a significant increase in the level of knowledge. Conclusions: Thus the structured teaching programme on knowledge regarding child abuse was effective.